Productivity and economics of soybean (Glycine max) as influenced by different tillage practices and phosphorus fertilization under conservation agriculture - NAYAK, SOMANATH; BEHERA, U K; MEENA, S L; SHIVAY, Y S (The Indian Journal of Agricultural Sciences, 2020)
Based on our findings, it can be concluded that soybean crop can be successfully raised with conservation agricultural (CA) practices with a reasonably high level of productivity and profitablity. The higher productivity and profitability was recorded under conservation agricultural practices involving zero-tillage-bed with wheat crop residue of 3.0 t/ha. The yield improvement of soybean with ZT–B + R was 16.2%, 10.96% and 5.3% compared with CT–R, ZT–R and ZT + R, respectively. The significantly highest gross (65000 ₹/ha), net returns (35100 ₹/ha) and B:C ratio (2.18) were obtained with ZT–B + R. Among phosphorus fertilization practices, soybean responded well up to 80 kg P2O5/ha (34.5 kg P/ha) as basal application with increase in crop productivity and profitablity. Yield improvement with 80 kg P2O5/ha was 21.6% and 13.9% compared to 0 and 40 kg P2O5/ha, respectively. However, application of 120 kg P2O5/ha (52.5 kg P/ha) didn’t show any significant increment in productivity and profitablity over 80 kg P2O5/ha.